Psittacine sex determination by radioimunoassay (RIA) of sex steroids using fecal samples - Dias, Eduardo Antunes; Oliveira, Cláudio Alvarenga de (Brazilian Journal of Veterinary Research and Animal Science, 2006)
For the current study, it were used fecal samples from 50 psittacines, previously sexed by PCR from blood cells. The fecal androgens and estrogens metabolites were extracted with PBS (Phosfate Buffer Saline) or PBS:Ethil Alchool (4:1) and measured by comercial radioimunoassay kits at the "Laboratório de Dosagens Hormonais" of the "Departamento de Reprodução Animal" of the "Faculdade de Medicina Veterinária e Zootecnia" of the "Universidade de São Paulo". The sex determination of the birds were performed using the confidence interval (95%) for transformed androgens values. 70% of birds had the sex confirmed by radioimunoassay. The results showed that further studies for sex determination on monomorphic birds by non-invasive techniques are necessary.